Elementary School Students' Understanding of Geometry Concepts Through the Manuk Dadali Dance Media - Firdaus, Yan Anita; Feny Rita Fiantika; Rusminati, Susi Hermin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to describe the understanding of geometry concepts of fifth grade elementary school students regarding angles through the application of the Manuk Dadali Dance media. This research is a qualitative research. The subjects in this research were fifth grade students at SDN Sedati Gede 2 Sidoarjo, including one subject with high ability, one subject with medium ability, and one subject with low ability. The data collection techniques used were written tests and interviews, while the research instruments used were written tests related to corner material which contained description questions and interview guidelines. The results of this study show that students with high ability were able to complete all the written tests correctly, students with moderate ability were not able to solve one written test question related to the addition of two or more angles correctly, and students with low ability were not able to write down the meaning of one rotation angle full exactly